Exploring the HRM-performance relationship: the role of creativity climate and strategy. Issue 3 (4th April 2016) - Heffernan, Margaret; Harney, Brian; Cafferkey, Kenneth; Dundon, Tony
Abstract : Purpose: – While an established stream of research evidence has demonstrated that human resource management (HRM) is positively related to organisational performance, explanations of this relationship remain underdeveloped, while performance has been considered in a narrow fashion. Exploring the relevant but often neglected impact of creativity climate, the purpose of this paper is to examine key processes (mediation and moderation) linking high-performance human resource practices with a broad range of organisational performance measures, including employee performance and HR performance. Design/methodology/approach: – The paper draws on a People Management Survey of 169 HR managers from top performing firms in the Republic of Ireland. Findings: – The findings provide general support for the role of creativity climate as a key mediator in the HRM-performance relationship. The impact of HPWS on performance is judged universal with little evidence of variation by strategic orientation. Practical implications: – Sophisticated HRM is found to directly impact a range of organisational performance outcomes. Creativity climate provides an understanding of the mechanisms through which such impact takes effect. Organisations should develop a clear and consistent HR philosophy to realise HR, employee and organisational performance. Originality/value: – The paper offers a more intricate understanding of the key factors shaping both the operation and impact of the HRM-performance relationship. Creativity climate offers an important vehicle to better understand how the HRM-performance relationship actually operates. The paper also highlights the potential of examining multiple organisational performance outcomes to offer more nuanced and considered insights.